PLA-PEKK-HAp-CS composite scaffold joining with friction stir spot welding - Singh, J.; Singh, R.; Kumar, R.; M. M., Rahman; Ramakrishna, S. (SAGE Publications, 2019)
This article reports joining feasibility of polylactic acid-polyether ketone ketone-hydroxyapatite-chitosan composite scaffold with consumable tool in friction stir spot welding (FSSW) as a novel process. Also, investigations have been made for mechanical, thermal, and morphological characteristics of the joints prepared. The results for joint strength are supported with axial/transverse force and interface temperature measurement for bone scaffolds. The FSSW process parameters, namely rotational speed, pin depth, and stirred time, have been varied to correlate the changes in force and temperature with mechanical and morphological properties. The results of the study highlighted that ultimate tensile strength (6.57 MPa) and flexural strength (139.2 MPa) were obtained best at 800 r/min rotational speed and 20 s stirring time with 2.5-mm pin depth